Ответы и объяснения

Лучший Ответ!
2013-03-29T09:51:28+00:00

(x-2)/(x+1)+(x+1)/(x-2)=4,25

x≠-1, x≠2

(x-2)^2+(x+1)^2=4,25*(x+1)*(x-2)

x^2-4x+4+x^2+2x+1=4,25(x^2-x-2)

2x^2-2x+5=4,25x^2-4,25x-8,5

2,25x^2-2,25x-13,5=0

225x^2-225x-1350=0

x^2-x-6=0

По теореме Виетта x=-2 и x=3

 

Ответ x=-2 и x=3

2013-03-29T10:03:05+00:00

х-2/х+1+х+1/х-2=4,25

((х-2)*(х-2))/(х+1)+((х+1)(х+1))/(х-2)-(х-2)*(х+1)*4,25=0

((х-2)^2+(х+1)^2-4,25(х-2)(х+1))/(х+1)(х-2)=0

(х^2-4х+4+х^2+2х+1-4,25х^2-4,25х+8,5х+8,5)/(х+1)(х-2)=0

-2,25х^2+2,25х+13,5=0

х не должен равняться -1

х не должен равняться 2

-х^2+х+6=0

D=1+24=25

√D=5

х=(-1+5)/-2=-2

х=(-1-5)/+2=3

Ответ:-2;3